Increased platelet reactivity as measured by plasma glycoprotein VI in gout. (17th November 2018) - Conway, Richard; Murphy, Claire-Louise; Madigan, Anne; Kavanagh, Patricia; Geraghty, Liz; Redmond, Niamh; Helbert, Laura; Carey, John J.; Dunne, Eimear; Kenny, Dermot; McCarthy, Geraldine M.
Abstract: Patients with gout have an increased risk of cardiovascular events. The glycoprotein VI (GPVI) receptor is found exclusively on platelets and megakaryocytes, is proteolytically cleaved upon platelet activation, and detectable in plasma as soluble GPVI (sGPVI). Therefore, elevated sGPVI is a marker of platelet activation and a risk marker for cardiovascular events. The aim of this study was to assess platelet activation, as measured by plasma sGPVI level in gout. Blood samples were taken from patients with gout or osteoarthritis, and from healthy volunteers. Demographic and clinical data were collected for all participants. Blood samples were processed as double-spun platelet-poor plasma. Plasma sGPVI levels were measured using enzyme-linked immunosorbent assay. Mann–Whitney U test was used to compare groups. In total, 91 patients were included, 27 during gout flare, 41 with intercritical gout, 23 with osteoarthritis, and 53 healthy controls. Median (interquartile range) sGPVI levels were 6.51 ng/mL (4.52, 8.41) in gout flare, 3.58 ng/mL (2.11, 5.55) in intercritical gout, 2.73 ng/mL (2.17, 3.72) in osteoarthritis, and 2.19 ng/mL (1.72, 3.31) in healthy controls. Plasma sGPVI levels in both gout groups were significantly increased compared to healthy controls ( p < 0.005 for each), in gout flare compared to osteoarthritis ( p < 0.005), and in gout flare compared to intercritical gout ( p = 0.001). There was no significant difference in sGPVI levels in gout patients with and without tophi or in those prescribed colchicine. We conclude that patients with gout exhibit platelet hyperactivity as demonstrated by elevated sGPVI levels. Platelet activation is exacerbated in gout, especially during gout flares.